Case Report: Isolated Epileptic Seizures Associated With Anti-LGI1 Antibodies in a 7-Year-Old Girl With Literature Review - Wang, Ying; Zhang, Wei-Hua; Wang, Yuan (Frontiers in Pediatrics, 2022)
We describe the case of a 7-year-old girl with anti-leucine-rich glioma-inactivated 1 (anti-LGI1) antibodies (Abs) who presented with isolated epileptic seizures. Her refractory focal seizures did not respond to anti-seizure medicines but responded rapidly to immunotherapy. She remained seizure-free at 2 years follow-up. Reviewing the literature, isolated epileptic seizures have not been reported as the phenotype of anti-LGI1 autoimmunity in children. Our study indicated that screening for anti-LGI1 Abs is necessary for children with severe and/or drug-resistant new-onset focal epileptic seizures.